Multilocus dnA sequencing of the whiskey fungus reveals a continental-scale speciation pattern - Scott, J.A.; Ewaze, J.O.; Summerbell, R.C.; Arocha-Rosete, Y.; Maharaj, A.; Guardiola, Y.; Saleh, M.; Wong, B.; Bogale, M.; O'Hara, M.J.; Untereiner, W.A. (Persoonia, 2016)
Baudoinia was described to accommodate a single species, B. compniacensis. Known as the 'whiskey fungus', this species is the predominant member of a ubiquitous microbial community known colloquially as 'warehouse staining' that develops on outdoor surfaces subject to periodic exposure to ethanolic vapours near distilleries and bakeries. Here we examine 19 strains recovered from environmental samples near industrial settings in North America, South America, the Caribbean, Europe and the Far East. Molecular phylogenetic analysis of a portion of the nucLSU rRNA gene confirms that Baudoinia is a monophyletic lineage within the Teratosphaeriaceae (Capnodiales). Multilocus phylogenetic analysis of nucITS rRNA (ITS1-5.8S-ITS2) and partial nucLSU rRNA, beta-tubulin (TUB) and elongation factor 1-alpha (TEF1) gene sequences further indicates that Baudoinia consists of five strongly supported, geographically patterned lineages representing four new species (viz. Baudoinia antilliensis, B. caledoniensis, B. orientalis and B. panamericana).